Children´s acceptance of taste of probiotic yogurt sweetened with xylitol, sorbitol and stevia - Lazo Navarro, Rocio (2024)
Objective: To determine the taste acceptance of a probiotic yogurt sweetened with xylitol, sorbitol and stevia in children from 4 to 9 years old. Material and Methods: This was an observational, cross-sectional and prospective study. The sample was 95 children from 4 to 9 years old from the Pérez Araníbar Puericultorio, Lima-Peru. They tasted a probiotic yogurt (Bifidobacterium Bb-12 strain) sweetened with three non-cariogenic sweeteners such as xylitol, sorbitol and stevia, and an unsweetened probiotic yogurt. The flavor preference test was based on the Birch & Sullivan methodology, to determine children'sacceptance and not acceptance of taste of sweeteners in a probiotic yogurt, and categorization according to a ranking of flavor preference ranking. The Chi-square and Friedman tests were used to analyze the variables. Results: A statistically significant difference was found associated with flavor acceptance according to Birch & Sullivan methodology for the sweeteners xylitol, sorbitol and stevia used to sweeten a probiotic yogurt (p<0.0001). Conclusion: Xylitol and stevia added to a probiotic yogurt presented the greatest taste acceptance among children aged 4 to 9 years. In addition, yogurt with unsweetenedprobiotic did not show children’s acceptance.